Gluten-free small bites : sweet and savory hand-held treats for on-the-go lifestyles and entertaining - Hunn, Nicole (Da Capo Lifelong Books, 2016)
"Small bites aren't just for fancy parties with twee hors d'oeuvres (and no small children in sight). Gluten-free guru Nicole Hunn shares recipes for portable foods fitting every imaginable occasion-mini quiche for your book club, crispy coconut shrimp for the office potluck, and handheld chicken pot pies the kids can devour on-the-go. Complete with bite-size sweets-mini eclairs, little apple pies-that no one can resist, Gluten-Free Small Bites has a recipe for every occasion-spicy or sweet, vegetarian or meaty, fancy or kid-friendly"--